SUSTAINABLE ECONOMIC DEVELOPMENT OF THE REGIONS AND INCREASING THE FINANCIAL AUTHORITY - Akramovich , Khasanov Bakhodir; Ismatovich, Alikulov Abdimumin; Karjaubay Tileubayevich Nurmanov; Sаidmurod Yаkhyoyeviсh Аtаmurodov; Risolat Bahodirovna Hasanova (Antis Publisher, 2025)
Objective: Today, in order to achieve high economic growth, it is one of the most urgent issues to develop scientific-methodical approaches and recommendations for the management of the region's financial potential and the scientific-methodological justification of the mechanism of inter-budgetary relations and its improvement, in order to improve the effectiveness of regional management. Method: In this regard, this article analyzes the regions' financial potential, budget policy and economic growth rates. Results: Based on this, scientific views, suggestions and recommendations are developed. Novelty: The article offers a scientific-methodical framework aimed at enhancing the effectiveness of inter-budgetary relations and regional financial management, contributing new insights to regional economic policy studies.